2017
DOI: 10.1016/j.drugalcdep.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experience effects on opioid use initiation, injection drug use, and overdose among persons with opioid use disorder

Abstract: Introduction Adverse childhood experiences are associated with the development of substance use disorders. With opioid use disorder, a growing concern in the United States, we were interested in examining the relationship between adverse experiences and three landmarks of opioid use: age of opioid initiation, injection drug use, and lifetime overdose. Methods Between May and December 2015, we interviewed consecutive persons seeking inpatient opioid detoxification. Participants were asked about age of opioid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 47 publications
9
115
0
1
Order By: Relevance
“…In addition, current research suggests that adverse childhood experiences increase the risk of substance abuse later in life, and that providing these women with appropriate behavioral therapy is a necessary adjunct to treatment and healing future generations within a family. 128 This section describes 2 types of care models that have been proposed for the treatment of pregnant women with OUD during pregnancy: (1) a collaborative care model, in which various agencies and health-care providers form a partnership to facilitate patient access to these resources and (2) a "1-stop shop" model, in which colocated resources are provided to patients at a dedicated office or other facility, often as part of a large health-care institution, such as a hospital or health-care center. Although both models of care provide treatment of these women and their families during pregnancy and in the postpartum period, they differ in how these services are delivered to patients.…”
Section: Care Models and Integration Of Services To Support Oud Managmentioning
confidence: 99%
“…In addition, current research suggests that adverse childhood experiences increase the risk of substance abuse later in life, and that providing these women with appropriate behavioral therapy is a necessary adjunct to treatment and healing future generations within a family. 128 This section describes 2 types of care models that have been proposed for the treatment of pregnant women with OUD during pregnancy: (1) a collaborative care model, in which various agencies and health-care providers form a partnership to facilitate patient access to these resources and (2) a "1-stop shop" model, in which colocated resources are provided to patients at a dedicated office or other facility, often as part of a large health-care institution, such as a hospital or health-care center. Although both models of care provide treatment of these women and their families during pregnancy and in the postpartum period, they differ in how these services are delivered to patients.…”
Section: Care Models and Integration Of Services To Support Oud Managmentioning
confidence: 99%
“…For example, adverse childhood experiences may contribute to all three: criminality, mental health disorders, and opioid misuse and use disorder. [49][50][51] Our hope is that our results do not perpetuate stigma but rather encourage the development of effective interventions for speci c populations.…”
Section: Discussionmentioning
confidence: 82%
“…[58] Possibilities include access to illicit drugs for purchase and use of drugs by friends and family members, as well as adverse childhood experiences or trauma. [51,[59][60][61] While the present study revealed an increased association of opioid misuse with marijuana compared to non-marijuana users, the relationship in the literature has been mixed. In the cases of marijuana dependence or abuse there is a positive relationship with opioid misuse.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings are also consistent with a few other studies that have shown a high rate of opioid use and other chemical dependencies in nonpregnant children and adolescents who have experienced sexual abuse, physical abuse, and other childhood traumas. [9][10][11][12][13][14] Conroy et al, in a study of 967 opioiddependent patients from Australia (588 males and 379 females), reported that females had a higher prevalence and greater severity of sexual abuse, whereas males had a higher prevalence of physical and emotional abuse. 10 Likewise, a study 30 years ago, involving 597 adolescent girls in treatment for substance abuse, reported that nearly 45% had a history of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%